Exploration of the role of the penicillin binding protein 2c (Pbp2c) in inducible β-lactam resistance in Corynebacteriaceae - Lavollay, Marie; Buon, Céline; Le Moigne, Vincent; Compain, Fabrice; Guyonvarch, Armel; Fonvielle, Matthieu (Frontiers in Microbiology, 2024)
Six genes encoding putative high molecular weight penicillin-binding proteins (Pbp) are present in the genome of the β-lactam-resistant strain Corynebacterium jeikeium K411. In this study, we show that pbp2c, one of these six genes, is present in resistant strains of Corynebacteriaceae but absent from sensitive strains. The molecular study of the pbp2c locus from C. jeikeium and its heterologous expression in Corynebacterium glutamicum allowed us to show that Pbp2c confers high levels of β-lactam resistance to the host and is under the control of a β-lactam-induced regulatory system encoded by two adjacent genes, jk0410 and jk0411. The detection of this inducible resistance may require up to 48 h of incubation, particularly in Corynebacterium amycolatum. Finally, the Pbp2c-expressing strains studied were resistant to all the β-lactam antibiotics tested, including carbapenems, ceftaroline, and ceftobiprole.